Composite graphite negative electrode material and preparation method and application thereof
By coating scale graphite on high sulfur coke and graphitization, composite graphite negative electrode materials are prepared, which solves the performance problems caused by excessive sulfur content in high sulfur coke raw materials, improves the rate performance and capacity of lithium-ion batteries, and reduces the rate performance and capacity of lithium-ion batteries. production costs.
Patent Information
- Application Number
- CN202411291388.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-13
AI Technical Summary
In the prior art, when high sulfur coke is used as the raw material for graphite negative electrode material, excessive sulfur content leads to an increase in voids and a larger specific surface area during graphitization treatment, hindering graphite growth, reducing rate performance and capacity, and increasing vulcanization or desulfurization treatment. Cost, it is difficult to meet higher demands.
By selecting high-sulfur coke as raw material, using binder to coat the scale graphite on the surface of high-sulfur coke, and performing granulation and graphitization, we prepare composite graphite negative electrode materials to avoid sulfurization or desulfurization treatment, and use the gaps of high-sulfur coke and the specific surface area increase the lithium ion embedding rate, reduce lithium consumption in SEI membrane, and improve capacity and compaction density.
It significantly improves the rate performance and capacity of lithium-ion batteries, reduces lithium consumption, improves compaction density, meets higher demands, and reduces production costs.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a composite graphite negative electrode material and a preparation method and application thereof. Background Art
[0002] With the rapid development of lithium batteries, the demand for artificial graphite, the main negative electrode material, is also increasing day by day. The common raw material for artificial graphite is petroleum coke, which is generally divided into low, medium and high sulfur coke according to the sulfur content in the industry. Low sulfur coke is coke with a sulfur content of less than 1%, while 1%-3% is called medium sulfur coke, and more than 3% is called high sulfur coke. At present, the petroleum coke used in large quantities for commercial use is low sulfur coke. Due to the tight supply of low sulfur coke, the cost is too high. In order to meet the needs of downstream battery cell factories, it is urgent to develop low-cost petroleum coke as a substitute. High sulfur coke has a cost advantage because of its cheap raw materials and large output, so many graphite manufacturers have begun to develop high sulfur coke as a raw material for graphite negative electrodes.
[0003] Since the sulfur content of high-sulfur coke is too high, during the graphitization process, the sulfur in the coke will overflow in the form of gas, which will cause an increase in graphite voids and an increase in specific surface area. At the same time, due to the influence of sulfur, the continuous growth of graphite is hindered, the crystals are smaller, the anisotropy of graphite is reduced, and the isotropy of graphite is increased. Its compaction, capacity and initial efficiency will all be significantly reduced. When high-sulfur coke is used as a raw material, it is usually first vulcanized or desulfurized during the preparation process to reduce the sulfur content in the high-sulfur coke, so as to ensure the compaction, capacity and initial efficiency of the graphite material. However, vulcanization or desulfurization treatment will increase the cost of the product while adding more steps.
[0004] At present, there are many high-sulfur cokes on the market used as fast-charging graphite raw materials, but their compaction, capacity and initial efficiency are difficult to meet higher demands. Therefore, how to balance the rate performance and capacity initial efficiency of high-sulfur coke artificial graphite is an urgent problem to be solved. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a composite graphite negative electrode material and a preparation method and application thereof. High-sulfur coke is selected as a raw material, and flake graphite is coated on the surface of the high-sulfur coke by a binder, and then granulated and graphitized to prepare the composite graphite negative electrode material. During the preparation process, no sulfurization or desulfurization is required. On the one hand, after graphitization, the high-sulfur coke has many voids and a large specific surface area, and the particles are highly isotropic, which can significantly increase the lithium ion embedding rate, thereby improving the rate performance of the graphite negative electrode material; on the other hand, coating flake graphite can reduce the lithium consumption during the formation of the SEI film, improve the first effect, and also provide more lithium embedding sites, thereby increasing the capacity. At the same time, because the surface layer is natural graphite, its structure is regular, and it can withstand higher pressure during rolling, so that the compaction density is increased.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing a composite graphite negative electrode material, the preparation method comprising the following steps:
[0008] The high-sulfur coke is coarsely crushed and finely crushed in sequence to obtain crushed high-sulfur coke, a binder, flake graphite and the crushed high-sulfur coke are mixed, and granulation, graphitization and post-treatment are performed in sequence to obtain the composite graphite negative electrode material;
[0009] The sulfur content of the high-sulfur coke is 3-5wt%.
[0010] The present invention selects high-sulfur coke as a raw material, coats the surface of the high-sulfur coke with flake graphite through a binder, and then undergoes granulation and graphitization treatment to prepare the composite graphite negative electrode material. During the preparation process, no sulfurization or desulfurization is required. On the one hand, after the high-sulfur coke is graphitized, there are many voids and a large specific surface area, and the particles are highly isotropic, which can significantly increase the lithium ion embedding rate, thereby improving the rate performance of the graphite negative electrode material; on the other hand, coating with flake graphite can reduce the lithium consumption during the formation of the SEI film, improve the first effect, and also provide more lithium embedding sites, thereby increasing the capacity. At the same time, because the surface layer is natural graphite, its structure is regular, and it can withstand higher pressure during rolling, so that the compaction density is increased.
[0011] Preferably, the high-sulfur coke is subjected to coarse crushing and fine crushing in sequence to obtain crushed high-sulfur coke.
[0012] Preferably, after the coarse crushing, millimeter-sized crushed materials are obtained.
[0013] Preferably, after the fine crushing, micron-sized crushed high-sulfur coke is obtained.
[0014] Preferably, the particle size D50 of the crushed high-sulfur coke is 10-14 μm, for example, 10 μm, 11 μm, 12 μm, 13 μm or 14 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0015] Preferably, the binder includes any one of oil-based asphalt, coal-based asphalt, epoxy resin or phenolic resin, or a combination of at least two of them. Typical but non-limiting combinations include a combination of oil-based asphalt and coal-based asphalt, or a combination of coal-based asphalt, epoxy resin and phenolic resin.
[0016] Preferably, the D50 of the flake graphite is 8-10 μm, for example, 8 μm, 8.5 μm, 9 μm, 9.5 μm or 10 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] Preferably, the carbon content of the flake graphite is greater than 92wt%, for example, it may be 92.5wt%, 94wt%, 96wt%, 98wt% or 99wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] Preferably, the mass ratio of the crushed high-sulfur coke to flake graphite is (60-85):(12-30), for example, it can be 60:12, 60:30, 70:15, 80:20, 85:12 or 85:30, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] Preferably, the mass ratio of the crushed high-sulfur coke to the binder is (60-85):(3-10), for example, it can be 60:3, 60:10, 70:5, 80:9, 85:3 or 85:10, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] Preferably, the granulation temperature is 900-1500°C, for example, 900°C, 1000°C, 1100°C, 1200°C, 1300°C or 1500°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] Preferably, the granulation time is 3-8 h, for example, 3 h, 4 h, 5 h, 6 h, 7 h or 8 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0022] Preferably, the granulation atmosphere is an inert atmosphere.
[0023] Preferably, the inert atmosphere comprises helium and / or nitrogen.
[0024] Preferably, after the granulation, the flake graphite is coated on the crushed high-sulfur coke.
[0025] Preferably, granulated material is obtained after the granulation.
[0026] Preferably, the particle size of the granulated material is 12-16 μm, for example, 12 μm, 13 μm, 14 μm, 15 μm or 16 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] Preferably, the temperature of the graphitization treatment is 2800-3200°C, for example, it can be 2800°C, 2900°C, 3000°C, 3100°C or 3200°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable, preferably 3000-3200°C.
[0028] Preferably, the graphitization treatment time is 24-48 hours, for example, it can be 24 hours, 30 hours, 36 hours, 42 hours or 48 hours, but is not limited to the listed values. Other unlisted values within the numerical range are also applicable, preferably 40-42 hours.
[0029] Preferably, the atmosphere of the graphitization treatment is an inert atmosphere.
[0030] Preferably, the inert atmosphere comprises helium and / or nitrogen.
[0031] Preferably, the post-treatment includes deagglomeration and demagnetization screening performed in sequence.
[0032] As a preferred technical solution of the present invention, the preparation method consists of the following steps:
[0033] (1) coarsely crushing and finely crushing high-sulfur coke with a sulfur content of 3-5 wt% in sequence to obtain micron-sized high-sulfur coke;
[0034] (2) mixing micron-sized high-sulfur coke, a binder and flake graphite in a ratio of (60-85):(3-10):(12-30) to obtain a mixture;
[0035] (3) granulating the mixture at 900-1500° C. for 3-8 hours to obtain granulated material;
[0036] (4) graphitizing the granulated material at 2800-3200° C. for 24-48 hours to obtain a graphitized material;
[0037] (5) sequentially performing depolymerization and demagnetization screening on the graphitized material to obtain the composite graphite negative electrode material;
[0038] The sulfur content of the high-sulfur coke in step (1) is 3-5wt%.
[0039] In a second aspect, the present invention provides a composite graphite negative electrode material, which is prepared by the preparation method described in the first aspect.
[0040] Preferably, the composite graphite negative electrode material comprises a core graphite and a flake graphite coating layer.
[0041] On the one hand, the inner core graphite after high-sulfur coke graphitization treatment has many voids and a large specific surface area, and the particles are highly isotropic, which can significantly increase the lithium ion embedding rate, thereby improving the rate performance of graphite negative electrode materials; on the other hand, the flake graphite coating can reduce the lithium consumption during SEI film formation, improve the first efficiency, and provide more lithium embedding sites, thereby increasing the capacity. At the same time, because the surface layer is natural graphite, its structure is regular and can withstand higher pressure during rolling, which increases the compaction density.
[0042] In a third aspect, the present invention provides an application of the composite graphite negative electrode material described in the second aspect, wherein the composite graphite negative electrode material is used for preparing a lithium-ion battery.
[0043] Compared with the prior art, the present invention has at least the following beneficial effects:
[0044] (1) The present invention selects high-sulfur coke as a raw material, coats the surface of the high-sulfur coke with flake graphite by a binder, and then undergoes granulation and graphitization treatment. During the preparation process, no sulfurization or desulfurization is required;
[0045] (2) After graphitization treatment, the high-sulfur coke of the present invention has many voids and a large specific surface area, and the particles are highly isotropic, which can significantly increase the lithium ion insertion rate, thereby improving the rate performance of the graphite negative electrode material;
[0046] (3) The flake graphite coated in the present invention can reduce the lithium consumption during the formation of the SEI film, improve the initial efficiency, and provide more lithium insertion sites, thereby increasing the capacity. At the same time, since the surface layer is natural graphite, its structure is regular and can withstand higher pressure during rolling, thereby increasing the compaction density. DETAILED DESCRIPTION
[0047] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0048] Example 1
[0049] This embodiment provides a method for preparing a composite graphite negative electrode material, and the preparation method comprises the following steps:
[0050] (1) coarsely crushing and finely crushing high-sulfur coke with a sulfur content of 3% in sequence to obtain micron-sized crushed high-sulfur coke with a D50 of 10±2 μm;
[0051] (2) mixing the crushed high-sulfur coke, oil-based asphalt, and flake graphite with a D50 of 9 μm and a carbon content of 95 wt% in a ratio of 80:5:15 to obtain a mixture;
[0052] (3) granulating the mixture at 1300°C for 6 h under a nitrogen atmosphere to obtain granules with a D50 of 12±2 μm;
[0053] (4) graphitizing the granulated material in a graphitization furnace at 3000° C. for 40 h under a nitrogen atmosphere to obtain a graphitized material;
[0054] (5) The graphitized material is sequentially depolymerized and dispersed and demagnetized and sieved to obtain the composite graphite negative electrode material.
[0055] Example 2
[0056] This embodiment provides a method for preparing a composite graphite negative electrode material, and the preparation method comprises the following steps:
[0057] (1) coarsely crushing and finely crushing high-sulfur coke with a sulfur content of 5% in sequence to obtain micron-sized crushed high-sulfur coke with a D50 of 14±2 μm;
[0058] (2) mixing the crushed high-sulfur coke, coal-based asphalt and flake graphite with a D50 of 8 μm and a carbon content of 92.5 wt% in a ratio of 85:3:12 to obtain a mixture;
[0059] (3) granulating the mixture at 900°C for 8 h under a nitrogen atmosphere to obtain granules with a D50 of 16±2 μm;
[0060] (4) graphitizing the granulated material in a graphitization furnace at 2800° C. for 48 h under a nitrogen atmosphere to obtain a graphitized material;
[0061] (5) The graphitized material is sequentially depolymerized and dispersed and demagnetized and sieved to obtain the composite graphite negative electrode material.
[0062] Example 3
[0063] This embodiment provides a method for preparing a composite graphite negative electrode material, and the preparation method comprises the following steps:
[0064] (1) coarsely crushing and finely crushing high-sulfur coke with a sulfur content of 4% in sequence to obtain micron-sized crushed high-sulfur coke with a D50 of 12±2 μm;
[0065] (2) mixing the crushed high-sulfur coke, phenolic resin and flake graphite with a D50 of 10 μm and a carbon content of 99 wt% in a ratio of 60:10:30 to obtain a mixture;
[0066] (3) granulating the mixture at 1500°C for 3 h under a nitrogen atmosphere to obtain granules with a D50 of 14±2 μm;
[0067] (4) graphitizing the granulated material in a graphitization furnace at 2800° C. for 48 h under a nitrogen atmosphere to obtain a graphitized material;
[0068] (5) The graphitized material is sequentially depolymerized and dispersed and demagnetized and sieved to obtain the composite graphite negative electrode material.
[0069] Example 4
[0070] The only difference between this embodiment and embodiment 1 is that, except for step (2) in which the micron-sized high-sulfur coke, the binder and the flake graphite are mixed in a ratio of 80:5:40, the rest is the same as embodiment 1.
[0071] Example 5
[0072] The only difference between this embodiment and embodiment 1 is that, except that the granulation temperature in step (3) is 800° C., the rest is the same as embodiment 1.
[0073] Example 6
[0074] The only difference between this embodiment and embodiment 1 is that, except for the granulation time in step (3) being 2.5 h, the rest is the same as embodiment 1.
[0075] Example 7
[0076] The only difference between this embodiment and embodiment 1 is that, except for the temperature of the graphitization treatment in step (4) being 2700° C., the rest is the same as embodiment 1.
[0077] Example 8
[0078] The only difference between this embodiment and embodiment 1 is that, except for the time of graphitization treatment in step (4) being 22 hours, the rest is the same as embodiment 1.
[0079] Comparative Example 1
[0080] The difference between this comparative example and Example 1 is that, except that no flake graphite is added in step (2), the rest is the same as Example 1.
[0081] Comparative Example 2
[0082] The difference between this comparative example and Example 1 is that, except for not performing step (3), the rest is the same as Example 1.
[0083] Comparative Example 3
[0084] The difference between this comparative example and Example 1 is that, except that the sulfur content of the sulfur coke in step (1) is 2%, the rest is the same as Example 1.
[0085] Test Method
[0086] The composite graphite negative electrode materials prepared in Examples 1-8 and Comparative Examples 1-3 were used to prepare negative electrode slurry according to the ratio of graphite: conductive agent: binder = 96:0.5:1.5:2, which was coated on copper foil, dried at 80°C, and then cut into 16 mm small discs. The electrolyte was 1 mol / L LiPF6 (EC:DMC:EMC=2:1:1), and the lithium sheet was used as the positive electrode to assemble into a CR2430 button battery, and the capacity, initial efficiency and rate performance were tested, and the test results were recorded in Table 1;
[0087] Table 1
[0088] Sulfur content Flake graphite ratio Capacity mAh / g First effect 2C / 0.1C Example 1 3% 15% 348 93.2% 14.3% Example 2 5% 12% 343 91.9% 15.7% Example 3 4% 30% 349 94% 12.8% Example 4 3% 40% 350 94.1% 12% Example 5 3% 15% 342 91.7% 12.7% Example 6 3% 15% 341 91.5% 12.5% Example 7 3% 15% 342 91.8% 12.8% Example 8 3% 15% 343 92% 12.9% Comparative Example 1 3% 0 340 90% 20.2% Comparative Example 2 3% 15% 343 91.9% 20.2% Comparative Example 3 2% 15% 346 88.5% 11.7%
[0089] The test results show that:
[0090] (1) It can be seen from Examples 1-8 and Comparative Examples 1-3 that the composite graphite negative electrode material prepared by the present invention, by selecting high-sulfur coke as the raw material, coating the surface of the high-sulfur coke with flake graphite with a binder, and then subjecting the material to granulation and graphitization treatment, has excellent rate performance and also improves the compaction density, capacity and first efficiency.
[0091] (2) It can be seen from Examples 1 and 4 that the composite graphite negative electrode material prepared by the present invention, by further optimizing the coating amount of flake graphite, can take into account rate performance, capacity and first efficiency.
[0092] (3) It can be seen from Example 1 and Examples 5-6 that the composite graphite negative electrode material prepared by further regulating the granulation temperature and time in the present invention has further improved rate performance, capacity and first efficiency.
[0093] (4) It can be seen from Example 1 and Examples 7-8 that the composite graphite negative electrode material prepared by further regulating the temperature and time of the graphitization treatment in the present invention has further improved rate performance, capacity and first efficiency.
[0094] (5) It can be seen from Example 1 and Comparative Examples 1-2 that the composite graphite negative electrode material prepared by the present invention by granulating and coating flake graphite on crushed high-sulfur coke can take into account rate performance, capacity and first efficiency.
[0095] (6) It can be seen from Example 1 and Comparative Example 3 that the composite graphite negative electrode material prepared by the present invention using high-sulfur coke as the raw material has excellent rate performance.
[0096] In summary, the present invention selects high-sulfur coke as a raw material, coats the surface of the high-sulfur coke with flake graphite through a binder, and then undergoes granulation and graphitization treatment to prepare the composite graphite negative electrode material. During the preparation process, no sulfurization or desulfurization is required. On the one hand, after the high-sulfur coke is graphitized, there are many voids and a large specific surface area, and the particles are highly isotropic, which can significantly increase the lithium ion embedding rate, thereby improving the rate performance of the graphite negative electrode material; on the other hand, coating flake graphite can reduce the lithium consumption during the formation of the SEI film, improve the first effect, and also provide more lithium embedding sites, thereby increasing the capacity. At the same time, because the surface layer is natural graphite, its structure is regular, and it can withstand higher pressure during rolling, which increases the compaction density.
[0097] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a composite graphite negative electrode material, characterized in that: The preparation method consists of the following steps: The high-sulfur coke is coarsely crushed and finely crushed in sequence to obtain crushed high-sulfur coke, a binder, flake graphite and the crushed high-sulfur coke are mixed, and granulation, graphitization and post-treatment are performed in sequence to obtain the composite graphite negative electrode material; The sulfur content of the high-sulfur coke is 3-5wt%.
2. The preparation method according to claim 1, characterized in that: The particle size D50 of the crushed high-sulfur coke is 10-14 μm; Preferably, the binder includes any one of oil-based asphalt, coal-based asphalt, epoxy resin or phenolic resin, or a combination of at least two thereof; Preferably, the D50 of the flake graphite is 8-10 μm; Preferably, the carbon content of the flake graphite is greater than 92 wt%.
3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the crushed high-sulfur coke to flake graphite is (60-85):(12-30); Preferably, the mass ratio of the crushed high-sulfur coke to the binder is (60-85):(3-10).
4. The preparation method according to any one of claims 1 to 3, characterized in that The granulation temperature is 900-1500°C; Preferably, the granulation time is 3-8h; Preferably, the granulation atmosphere is an inert atmosphere; Preferably, after the granulation, the flake graphite is coated on the crushed high-sulfur coke.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The temperature of the graphitization treatment is 2800-3200°C, preferably 3000-3200°C; Preferably, the graphitization treatment time is 24-48h, preferably 40-42h; Preferably, the atmosphere of the graphitization treatment is an inert atmosphere.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The post-treatment includes deagglomeration and demagnetization screening performed in sequence.
7. The preparation method according to claim 1, characterized in that: The preparation method consists of the following steps: (1) coarsely crushing and finely crushing high-sulfur coke having a sulfur content of 3-5 wt% in sequence to obtain micron-sized high-sulfur coke; (2) mixing micron-sized high-sulfur coke, a binder and flake graphite in a ratio of (60-85):(3-10):(12-30) to obtain a mixture; (3) granulating the mixture at 900-1500° C. for 3-8 hours to obtain granulated material; (4) graphitizing the granulated material at 2800-3200° C. for 24-48 hours to obtain a graphitized material; (5) sequentially performing depolymerization and demagnetization screening on the graphitized material to obtain the composite graphite negative electrode material; The sulfur content of the high-sulfur coke in step (1) is 3-5wt%.
8. A composite graphite negative electrode material, characterized in that: The composite graphite negative electrode material is prepared by the preparation method according to any one of claims 1 to 7.
9. The composite graphite negative electrode material according to claim 8, characterized in that: The composite graphite negative electrode material comprises a core graphite and a flake graphite coating layer.
10. An application of the composite graphite negative electrode material as claimed in claim 8 or 9, characterized in that: The composite graphite negative electrode material is used for preparing lithium ion batteries.
Citation Information
Patent Citations
Lithium ion secondary battery negative electrode material and preparation method thereof
CN104140093A
Production method of composite artificial graphite anode material
CN105236395A
Method for preparing composite graphite negative electrode material
CN105990581A
Preparation method of lithium ion battery negative-electrode material
CN107651680A
A preparation method of a graphite negative electrode material for improving coating performance and a material thereof
CN109148852A
